The significance of green entrepreneurial self-efficacy: Mediating and moderating role of green innovation and green knowledge sharing culture - Guo, Jingyi (Frontiers in Psychology, 2022)
Green entrepreneurial self-efficacy refers to individuals' conviction that they can contribute to solving environmental issues and shows self-assurance in their efforts to protect the environment. The present investigation attempts to determine the role of employees' green entrepreneurial self-efficacy in the green innovation of organizations. It is also proposed that green innovation positively impacts organizational environmental, economic and social performance. This study also evaluates the mediating role of green innovation and moderating role of the green knowledge-sharing culture. This study tested the hypothesis using a partial least squares structural equation modeling by applying smart PLS software. A total of 289 employees from SMEs in China were targeted for data collection. The results confirmed that green entrepreneurial self-efficacy positively impacts green innovation. Additionally, the findings verified that green innovation positively enhances firms' environmental, economic, and social performance. The results validate the mediating role of green innovation. The moderating results revealed that green knowledge-sharing culture does not play a moderating role in proposed relationships. This study serves the existing body of literature by providing empirical evidence on the significance of green entrepreneurial self-efficacy. The study outcomes highlighted the bridging role of employees' green entrepreneurial self-efficacy for firms' green innovation. The results also offer companies a road map for how staff members' green entrepreneurial self-efficacy might help the businesses to improve their performance in terms of the environment, economy, and society.